Payment of Compensation for Officials Who Did Not Implement the Decision of the State Administrative Court - Aries Saputro (Universitas Airlangga, 2019)
Unlawful Acts by the Agency and/or Government Official (onrechtmatige overheidsdaad) carried out in exercising their authority, which may result in the public, individuals and private legal entities to bring a civil suit to the District Court, to obtain compensation. Meanwhile, the public, individuals or legal entities may request an administrative claim for the issuance of a State Administration Decree by a Government Official to the State Administrative Court. The Court's Decision is a representation of legal considerations by the Judge which is recognized as